that's the solution of the system
X=3
y=1
Use substitution method starting with the first equation substitute y in the second equation
Answer:
f(x) = -7x² - x + 2
Step-by-step explanation:
Quadratic functions are set up in the form ax² + bx + c. f(x) = 0x² + 3x -3 is also set up in this format but 0x² would simplify to 0 which means the equation is actually f(x) = 3x-3 and does not fit in the quadratic function format. The other equations are also not set up in ax² + bx + c.
Answer:
-0.2588 but rounded is -0.26
Step-by-step explanation:
I don't believe you can. It would end up being 1/2 for all the terms so just leaving it as a fraction would be neater.